Михайло Котурницький (recte Еразм Кобилянський) у контексті взаємин з Іваном Франком - Салій, О. (Слово і Час, 2022)
У статті йдеться про польського громадсько-політичного діяча другої половини ХІХ — початку ХХ ст. Еразма Кобилянського, який відіграв негативну роль у житті Івана Франка. Саме через нього 1878 р. Франко став
одним із підсудних у гучному судовому процесі над соціалістами в Галичині.
Стаття висвітлює мало відомі дослідникам віхи біографії цього діяча.
Розглянуто контакти І. Франка й Е. Кобилянського, поширення соціалістичних ідей у Галичині в 1870-х роках. Уперше проаналізовано рукописні листи Кобилянського до Франка. З’ясовано, хто був автором поетичної збірки «Ukrainki» (Львів, 1884), підписаної псевдонімом Mychałko. The paper refers to the Polish social and political figure of the 2nd half of the 19th — the
early 20th century — Erazm Kobylianskyi. He was an emissary and a socialist and played
a negative role in the life of Ivan Franko. Because of the E. Kobylianskyi I. Franko became
one of the defendants in a high-profile trial of the socialists in Galicia in 1878. The paper
outlines biography of this person, little known to Ukrainian researchers. Due to the fact that
Kobylianskyi was a conspirator and had many aliases, not all circumstances of his life have
been clarified yet. The researcher managed to find out some details of his biography in the
memoirs of his contemporaries.
The main part of the study is focused on the issue of life contacts of I. Franko and
E. Kobylianskyi. They met in connection with the pretrial investigation in the case of the
socialist process in Galicia: that’s why an attention is also paid to certain aspects of this
issue (in particular, the topic of socialism in Galicia of the 1870s, the trial of Franko and
other accused). Franko himself never learned the real surname of Kobylianskyi and believed
that he was dealing with Mykhailo Koturnytskyi (it was the most oft en used pseudonym of
Kobylianskyi in Galicia).
Polish authorities in Galicia of those days accused I. Franko of participating in a secret
socialist society, in fact because of a letter by M. Drahomanov, which Kobylianskyi secretly
brought from Switzerland to Lviv and had to pass it to M. Pavlyk. Can be considered as a
matter of chance the fact that the police confiscated those letters? Could Kobylianskyi be
a figurehead? The paper proposes answers to these questions with reference to reputable
researchers and articles by Ivan Franko.
Also, the study provides an analysis of the handwritten letters of Erazm Kobylianskyi to
Ivan Franko from 1886. It is found out who was the author of the poetry collection “Ukra inki”,
published in 1884 in Lviv under the pseudonym Mychałko (Ivan Franko thought it was
Kobylianskyi but was wrong).